МЕХАНИЗАЦИЯ ТЕХНОЛОГИИ ПОСАДКИ ЧЕСНОКА (Proceedings of Scientific Conference on Multidisciplinary Studies, 2023)
The article presents information about the agrotechnology of garlic cultivation and its significance today. In addition, it was noted that the relevance of the process of planting garlic cloves is an important issue.